Productive Ward: Releasing Time to Care, or capacity for compassion: results from a longitudinal study of the quality improvement initiative. (March 2017) - White, Mark; Butterworth, Tony; Wells, John SG
Recent concerns about the poor quality of healthcare and diminishing compassion within patient care have prompted many healthcare organisations to adopt 'compassion' and 'care' into their value and mission statements. Productive Ward: Releasing Time to Care (PW) is a quality improvement (QI) programme designed to meet the value and mission intentions around quality and compassion. The purpose of this study is to measure the impact that PW has on direct patient care (DPC) times and the capacity of ward-based teams to provide compassionate care. This study used an exploratory longitudinal, cohort design (with an experimental test outcome, using a matched control group) to examine DPC times and 'engagement' (the antithesis of 'burnout' and 'compassion fatigue') amongst ward-based teams involved the PW QI initiative in Ireland. Ward-based teams involved in PW reported higher baseline levels of 'engagement' (vigour, absorption and dedication) compared to a control group which remained unchanged after a 12-month period. DPC times improved in just over half the study sites, but no significant changes were observed. No statistically significant relationships between 'engagement' and DPC were established. This study demonstrates that PW does not necessarily 'release time to care' in every instance and that many factors influence this. Compared to a control group it does, however, show encouraging signs that it may engage ward-based teams, thus creating some of the conditions and capacity in which compassion and quality can flourish.